ANALYSIS AND EVALUATION OF LAW WITH THE SCOPE OF MATERIALS IN THE FIELD OF COPYRIGHT WORK RELATED TO SPATIAL PLANNING - Budiman NPD Sinaga (NOMOI Law Review, 2021)
Further arrangements in the Regional Regulation if not done carefully can cause new problems, the District and Municipal Governments can not simply be seen as subordinate products of the Provincial Regulation and should not be contrary to the Provincial Regulation. Therefore, the establishment of provincial regulation can not be done without regard to the interests of the District and the City. It is very good if in the establishment of the Provincial Regulation opened the opportunity for the District and the City to participate. The research method used is normative juridical. The results showed that based on the Copyright Act there are several material content of the Spatial Planning Law and The Regulation of RTRWP Sumut that must be changed and even eliminated, among others regarding licensing directives. In addition, some provisions of the Copyright Act can reduce and even eliminate legal certainty such as the possibility of regulation of certain content material through provincial regulations or governor regulations or types of legislation from the Central Government.Keyword: Cipta Kerja, Peraturan Daerah, Provinsi.